Brownian dynamics simulations of analytical ultracentrifugation experiments exhibiting hydrodynamic and thermodynamic non-ideality. Issue 45 (13th November 2017) - Uttinger, M. J.; Walter, J.; Thajudeen, T.; Wawra, S. E.; Peukert, W.
Abstract : An extended Brownian Dynamics based algorithm incorporating hydrodynamic and thermodynamic non-ideality is presented. Abstract : Hydrodynamic and thermodynamic non-ideality are important phenomena when studying concentrated and interacting systems in analytical ultracentrifugation (AUC). Here we present an extended Brownian Dynamics (BD) based algorithm which incorporates hydrodynamic and thermodynamic non-ideality. It can serve as an independent and versatile approach for the theoretical description of interparticulate interactions in AUC, as it allows tracking the trajectory of individual particles. Concentration dependencies of the sedimentation and diffusion coefficient have been implemented and validated for the extended BD model. For monodisperse systems, it is shown that profiles obtained by BD are in excellent agreement with well-established Lamm equation solvers. Moreover, important limits and restrictions of current Lamm equation based analysis methods are discussed. In particular, BD allows modeling and evaluation of AUC data of non-ideal polydisperse systems. This is relevant as most nanoparticulate systems are polydisperse in size. Here, a simulation for a polydisperse system including concentration effects is presented for the first time.